Benchmarks on the intervention of the Ombudsman in ensuring the safety and protection of the citizen - Goia , Simina Ioana (International Journal of Legal and Social Order, 2023)
In recent decades, on the European continent, the Ombudsman ( also known as Ombusman, Defender, Mediator, etc ) is organized and operates as an autonomous institution that acts independently, impartially and transparently against maladministration, human rights violations affecting individuals or legal entities.